1995
DOI: 10.1002/bio.1170100306
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and inhibition of luminol chemiluminescence by phenolic acids

Abstract: We explored the behaviour of a series of phenolic acids used as enhancers or inhibitors of luminol chemiluminescence by three different methods to determine if behaviour was associated with phenolic acid structure and redox character. All the phenolic acids inhibited chemiluminescence when hexacyanoferrate (III) was reacted with the phenolic acids before adding luminol. The redox character of these compounds was clearly related to structure. When hexacyanoferrate(III)-luminol-O2 chemiluminescence was initiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…[9] Also the CL of the system enhanced by 4-iodophenol was applied to hydrogen peroxide determination. [10,11] In several instances the analyte acts as inhibitor of the reference reaction, producing a decreasing in the speed of the CL reaction. [1] This situation can be used to develop analytical methodologies to determine low concentrations of the inhibitor based on CL inhibition kinetic.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Also the CL of the system enhanced by 4-iodophenol was applied to hydrogen peroxide determination. [10,11] In several instances the analyte acts as inhibitor of the reference reaction, producing a decreasing in the speed of the CL reaction. [1] This situation can be used to develop analytical methodologies to determine low concentrations of the inhibitor based on CL inhibition kinetic.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism is very complex and still under discussion (Diaz et al, 1995). The results of the enhanced luminollHRP reaction strongly depend on the reaction conditions: pH, relative luminol/enhancer concentration, HRP concentration, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the three chemiluminescence reagent systems (luminol and permanganate) have been used to detect a wide range of other compounds, including many with phenolic functionality (16)(17)(18). The reaction of phenolic compounds with cerium(IV) and rhodamine B has been less extensively explored, but Cui and 91 co-workers have recently shown that numerous phenols respond to a closely related reagent system consisting of cerium(IV) and rhodamine 6G (19).…”
Section: Introductionmentioning
confidence: 99%